TRADISI UANG PANAI’ SEBAGAI BUDAYA BUGIS (STUDI KASUS KOTA BITUNG PROPINSI SULAWESI UTARA) - Daeng, Reski; Rumampuk, Selvie; Damis, Mahyudin (HOLISTIK, Journal Of Social and Culture, 2019)
There is one value or philosophy of life in the Bugis tribe namely Siri’ (shame) or better known as Siri’ na pesse’. This Siri’ culture affects many joints of social life in south Sulawesi, even hierarchically has shaped the character and mentality of the people of south Sulawesi it self. As well as the marriage system that is very thick with siri' culture because marriage is considered the right moment for the whole family to show their dignity’s.  This is the case for the Bugis tribe in Bitung City who up hold siri’ values so that in this modern era Bugis indigenous communities there still strongly maintain the tradition of Panai Money 'which is one of the main conditions and is considered an ideal marriage in the Bugis tribe.  The initial form of Panai money 'as a form of appreciation to women, turned into an arena of social prestige that took the name of siri', the higher the social and level of stratification women have the higher the nominal value of their customary money.  In this case it can be said that Panai Money as part of the culture turned into a disaster and made people feel anxious. No wonder the marriage is canceled only because of the Panai' money which is less than what the bride asks because she remains adamant to the nominal she wants. If the request is not able to be fulfilled then the application process will be rejected, as a result the road taken by lovers who have loved one another is eloping (Silariang).  Keywords: marriage, tradition, panai’ money